LATAR BELAKANG TERBENTUKNYA CLIQUE THE ALLAY'S DAN FAKTOR-FAKTOR YANG MENDORONG KEKOHESIFAN ANTAR ANGGOTANYA - Christiara Ully Ully (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
Abstract This research aims to determine the formed background of The Allay's clique and the factorsthat push cohesiveness among its member. The approach used in this research is a qualitative approach with phenomenology qualitative technique. This research's subjects are five second grade of junior high school earlyadolescence females. The data collection techniques were used are survey, semi-structured interviews, field notes, and documentation. Data were analyzed by using qualitative data analysis techniques and data validity checking techniques with data triangulation based on sources and methods. The results of this study indicate that the formed background The Allay's clique is initially due to the intensity of frequent meetings. It supports their verbal interactions, and then through the interaction they find their common similarities, such as like the same type of food and music. They also like to do the same things. This clique cohesiveness built through intensive interaction among its members. Interaction is also occurred by physical, non-verbal and emotionally, when the five members spent much of their spare time together, both within and outside the school environment. The members of the clique have the same goal, which is self-actualization. Clique cohesiveness is also influenced by the structure, roles, norms, personal relationships among its members and sense of groupness that makes each member is felt as a unity. Keywords: Clique, Early Adolescence, Female Friendship, Group, Cohesiveness